Girls. [videorecording (DVD)] The complete fifth season - Dunham, Lena, 1986- (Home Box Office, 2017)
The return of the highly anticipated fifth season of the award-winning hit comedy series that follows the assorted humiliations and triumphs of a group of girls in their mid-20s, each facing new challenges in life and love this season.